We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
67
4
avatar+210 

Compute \(1 \cdot \frac {1}{2} + 2 \cdot \frac {1}{4} + 3 \cdot \frac {1}{8} + \dots + n \cdot \frac {1}{2^n} + \dotsb.\)
 

 Apr 12, 2019
 #3
avatar
+1

sumfor(n, 1, 1000, n/(2^n) = 2

 Apr 12, 2019
 #4
avatar+22188 
+2

Compute 

\(1 \cdot \dfrac {1}{2} + 2 \cdot \dfrac {1}{4} + 3 \cdot \dfrac {1}{8} + \dots + n \cdot \dfrac {1}{2^n} + \dotsb\)

 

 

\(\text{Let $x = \dfrac{1}{2} \quad|x|<1$ } \)

 

Now we have:  \(\displaystyle s= \sum \limits_{n=1}^{\infty} nx^n \)

 

Let the progression to be summed be put equal to s:

\(s = x+2x^2+3x^3+4x^4+\cdots + nx^n +\cdots\)

 

It is divided by \(x\) and multiplied by \(dx\) then

\(\dfrac{s\ dx}{x} = dx +2x\ dx+3x^2\ dx+4x^3\ dx+\cdots + nx^{n-1}\ dx +\cdots \)

 

and with the integrals taken this equation is found
\(\displaystyle \int \dfrac{s\ dx}{x} = x +x^2+x^3+x^4 +\cdots + x^n + \cdots = \dfrac{x}{1-x} \quad \text{ infinite geometric progression }\)

 

Therefore from the equation:
\(\displaystyle \int \dfrac{s\ dx}{x} = \dfrac{x}{1-x}\)


on differentiation s is found. For the equation becomes:
\(\begin{array}{rcll} \displaystyle \dfrac{s}{x} &=& \dfrac{x}{1-x}\left( \dfrac{1}{x}- \dfrac{(-1)}{1-x} \right) \\\\ &=& \dfrac{1}{1-x} + x(-1)(1-x)^{-2}(-1) \\\\ &=& \dfrac{1}{1-x} + \dfrac{x}{(1-x)^2} \\\\ &=& \dfrac{1-x+x}{(1-x)^2} \\\\ &=& \dfrac{1 }{(1-x)^2} \end{array}\)

 

thus there is produced:
\(\displaystyle s = \dfrac{x}{(1-x)^2} \\\)

So  \(\text{let $x = \dfrac{1}{2} $}:\)

 

\(\begin{array}{|rcll|} \hline s &=& \dfrac{ \dfrac{1}{2} } {\left(1-\dfrac{1}{2} \right)^2} \\\\ &=& \dfrac{ \dfrac{1}{2} } {\left( \dfrac{1}{2} \right)^2} \\\\ &=& \dfrac{ 1 } { \dfrac{1}{2} } \\\\ \mathbf{s} & \mathbf{=} & \mathbf{2} \\ \hline \end{array}\)


finally
\(\displaystyle 1 \cdot \dfrac {1}{2} + 2 \cdot \dfrac {1}{4} + 3 \cdot \dfrac {1}{8} + \dots + n \cdot \dfrac {1}{2^n} + \dotsb = 2\)

 

laugh

 Apr 12, 2019

15 Online Users

avatar
avatar
avatar
avatar
avatar